Southern folk medicine, 1750-1820 - Moss, Kay (University of South Carolina Press, 1999)
The author "inventories the medical ingredients and practices adopted by physicians, herb women, yeoman farmers, plantation mistresses, merchants, tradesmen, preachers, and quacks alike ... [and] shows how families passed down cures as heirlooms, how remedies crossed cultural and ethnic boundaries, and how domestic healers compounded native herbs and plants with exotic ingredients."--Jacket.
Keywords: Traditional medicine -- Southern States -- History.; Traditional medicine -- Southern States -- Formulae, receipts, prescriptions.; Medicine, Popular -- Formulae, receipts, prescriptions.; Folklore -- Southern States.; Southern States -- Social life and customs.; Folklore.; Medicine, Traditional -- history; Folklore; Formularies as Topic; Southeastern United States; Médecine traditionnelle -- États-Unis (Sud) -- Histoire.; Médecine traditionnelle -- États-Unis (Sud) -- Formules et recettes.; Médecine traditionnelle -- États-Unis (Sud) -- Formules et recettes -- Ouvrages de vulgarisation.; Folklore -- États-Unis (Sud); États-Unis (Sud) -- Mœurs et coutumes.; Médecine -- Ouvrages de vulgarisation -- Formules et recettes.; folklore (culture-related concept); PSYCHOLOGY -- Psychotherapy -- General.; Manners and customs; Medicine, Popular; Traditional medicine; Southern States; History; Prescriptions, formulae, receipts, etc.